Sensitive Detection of Antibodies in Patients with Acute Coxiella Burnetii Infection. (March 2022) - Menge, B.; Klemens, J.M.; Mentz, J.; Dieckmann, K.; Saschenbrecker, S.; Tran, K.H.; Hetherington, M.; Steinhagen, K.
Abstract : Purpose: Coxiella burnetii bacteria cause a zoonotic disease called Q fever. Differentiation between acute and chronic Coxiella infection is possible via serological detection of specific antibodies against Coxiella surface lipopolysaccharides, which exhibit antigenic phase variation over the disease course (acute: IgM/IgG against phase 2 antigens; chronic: IgG against phase 1 antigens). Here, we evaluated the diagnostic accuracy of three phase-specific Anti-Coxiella burnetii ELISAs from EUROIMMUN. Methods & Materials: The study included sera from 23 patients with acute Coxiella infection (23 primary, 17 follow-up samples) and 12 patients with chronic Coxiella infection (12 primary, 6 follow-up samples). The infection status had been classified based on composite results obtained by the SERION ELISA classic Coxiella burnetii Phase 2 IgM/IgG (Virion\Serion) and in-house complement fixation tests (CFT) based on Virion\Serion Phase 1 and 2 antigens. 47 samples were classified as seronegative based on SERION ELISA classic Coxiella burnetii Phase 2 IgM/IgG (Virion\Serion). Samples were analysed using Anti-Coxiella burnetii Phase 2 ELISA (IgM/IgG) and Anti-Coxiella burnetii Phase 1 ELISA (IgG) (EUROIMMUN). Results: The Anti-Coxiella burnetii ELISAs correctly identified acute-phase and chronic-phase marker for an infection (detection rates = 100%). 5 of the primary acute-phase samples were IgM negative or borderline in the SERION ELISA classic Coxiella burnetii Phase 2 IgM/IgG but positive in the Anti-Coxiella burnetii Phase 2 ELISA (IgM). The respective follow-up samples were positive for acute infection and indicated seroconversion. In the negative panel, assay specificities amounted to 97.9% (Phase 2 IgG and Phase 1 IgG) and 78.7% (Phase 2 IgM). Conclusion: The EUROIMMUN Phase 2 IgM ELISA provides higher sensitivity for detection of antibodies in the acute phase, enabling early diagnosis of Coxiella infections. Anti- Coxiella reactive samples in the preselected negative panel could include false positives due to cross-reactivity (with antibodies against other gram-negative bacteria or interferences with e.g. rheumatoid factors or autoantibodies) or a low assay specificity. Alternatively, they may represent true positive results due to lower sensitivity of the comparison test or previous infection with Coxiella . Confirmation would require follow-up testing. Overall, the EUROIMMUN Anti-Coxiella burnetii ELISAs are sensitive assays to support the laboratory diagnosis of a Coxiella infection.